Neglected sleep quality problems in women with gestational diabetes mellitus: a multi-center cross-sectional study - Jingya Yu; Zhixiang Chen; Yanhan Chen; Xingyu Wang; Zhongchen Luo; Jili Fan; Lingyao Chen; Qinghua Zhao; Jiao Tang (BMC Pregnancy and Childbirth)
Abstract Background Gestational diabetes mellitus (GDM) is the most common complication of pregnancy, affecting an estimated 16.7% of live births worldwide, which translates to approximately 21 million cases annually. Although poor sleep quality is a prevalent concern in this population, most existing studies predominantly focus on the impact of sleep disorders on GDM, rather than directly assessing sleep quality in women diagnosed with GDM. This study aimed to investigate sleep quality and its associated factors specifically among women with GDM. Methods We originally aimed to include 287 women with GDM; ultimately, 618 were invited, of whom 393 participated in the survey through a convenience sampling method at the obstetric clinics of four general tertiary hospitals in Chongqing, China, from June to August 2022. Data were collected utilizing sociodemographic characteristics, the Pittsburgh Sleep Quality Index (PSQI), the Sleep Hygiene Scale, and the Pregnancy-related Anxiety Scale (PrAS). We employed linear regression analysis to identify factors associated with sleep quality. Results The PSQI score of participants was (5.83 ± 3.41). Notably, 43.77% of participants reported an actual sleep duration of less than 8 h per night, whereas 45.55% experienced poor sleep quality. Worrying during the day about your inability to fall asleep (β = 0.204, P < 0.01), body image concern (β = 0.159, P < 0.01), going to bed thirsty (β = 0.160, P < 0.01), educational attainment (β=-0.150, P < 0.01), avoidance (β = 0.124, P < 0.01), sleep disturbed by bed partner’s sleep (β = 0.126, P < 0.01), and worrying as you prepare for bed about your inability to fall asleep (β = 0.137, P < 0.05) significantly affected the sleep quality of participants. Conclusions The study revealed a high prevalence of insufficient sleep duration and poor sleep quality among women with GDM, which was significantly influenced by inadequate sleep hygiene habits and pregnancy-related anxiety. These findings enhance our understanding of the factors affecting sleep quality in this population and underscore the necessity for healthcare professionals to timely identify sleep disorders. Implementing appropriate interventions, such as the development of educational programs focused on sleep hygiene and body image acceptance through cognitive behavioral therapy, could enhance the quality of care for women with GDM.